ESPANOL: Cannabis Sativa causes and consumption in adolscents from 15 to 19 years old. Otavalo Ecuador 2020-2021 (La U Investiga, 2021)
Cannabis Sativa is currently the most widely used illegal drug in the world, increasing day by day on a recurring basis in adolescents and young people. Cannabis Sativa is a plant of Asian origin, widely introduced in subtropical regions of the world, it is characterized by containing a large family of compounds called Cannabis and cannabinoids, an addictive substance that generates effects such as inhibition of sympathetic action and conditions that produce pleasant euphoria, sensation relaxation, loss of sense of identity and cardiac stress The objective of this research was to determine the causes and consumption of Cannabis Sativa in students of the República  del Ecuador Educational Unit of the Otavalo Canton. Cross-sectional descriptive study, non-experimental quantitative design, which included a sample made up of 124 third year high school students, in the months of Sep 2020 to Jun 2021, sociodemographic variables were collected and related to the causes of the consumption of this substance, to which was applied a survey validated by Dusi, Drug Use Screening Inventory / Montevideo Version, consisting of 32 items. The main causes are associated with social factors, prevailing elements generated by disorders in areas such as; family, social environment, educational center, educational days, and lack of communication with educators, predisposing the investigated group to consume this substance. Conclusion. It is shown that more than 80% of students consumed Cannabis Sativa, being the most used drug among adolescents, since it is the most easily accessible, after tobacco and alcohol.